THE ROLE OF THE EDUCATION SYSTEM IN POVERTY REDUCTION - Ne’matjonov Asadbek; Egamberdiyev Shavkatbek (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation. The article analyzes the important role of the educational system in poverty reduction. The impact of education on economic and social empowerment, skill development,  vocational  education,  and  the  importance  of  innovative  education programs in combating poverty are examined. At the same time, issues of the quality of education, its equal access and integration with public policy are discussed. The article  provides  strategic  recommendations  for  states  and  organizations,  showing practical ways to reduce poverty through the development of an educational system. This work highlights the contribution of education to the sustainable development of society.